1994
DOI: 10.1007/s001250050084
|View full text |Cite
|
Sign up to set email alerts
|

Nerve conduction and aldose reductase inhibition during 5 years of diabetes or galactosaemia in dogs

Abstract: To evaluate the role of excessive polyol pathway activity in the pathogenesis of nerve disorders in diabetes mellitus, nerve conduction velocity was measured in motor nerves of diabetic dogs given an aldose reductase inhibitor (Sorbinil) or placebo, and also in non-diabetic dogs made experimentally galactosaemic. The nerve conduction velocity slowly declined in the diabetic placebo group, becoming significantly less than normal by the fifth year of the study, and the decline was prevented by administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 18 publications
1
49
0
2
Order By: Relevance
“…For example, a long-term AR inhibition in diabetic dogs prevented sorbitol accumulation in erythrocytes and even diabetic neuropathy, but showed no beneficial effect on renal structure or albuminuria. It failed to prevent retinopathy or thickening of the capillary basement membrane in the retina, kidney and muscle [121,122]. The similar results were observed in a transgenic rat model with human AR cDNA.…”
Section: Summary and Perspectivesupporting
confidence: 71%
“…For example, a long-term AR inhibition in diabetic dogs prevented sorbitol accumulation in erythrocytes and even diabetic neuropathy, but showed no beneficial effect on renal structure or albuminuria. It failed to prevent retinopathy or thickening of the capillary basement membrane in the retina, kidney and muscle [121,122]. The similar results were observed in a transgenic rat model with human AR cDNA.…”
Section: Summary and Perspectivesupporting
confidence: 71%
“…In diabetic models, inhibitors of the first enzyme in the pathway, aldose reductase, prevent or correct nerve conduction velocity (NCV) and regeneration deficits [2][3][4][5][6][7][8][9][10][11][12][13]. Clinical trials of aldose reductase inhibitors (ARIs) have shown modest improvements in neurological symptoms, NCV, sensory measures, and an increase in nerve fibre regeneration [14-17] despite a less effective polyol pathway blockade than was found necessary for functional effects in animal studies [6,10,18].…”
mentioning
confidence: 99%
“…There are four major hypotheses about hyperglycemia induced diabetes complications which are (i) accelerated glucose flux through polyol pathway [3]; (ii) activation of protein kinase C (PKC) isoforms through de novo synthesis of the lipid second messenger diacylglycerol induced by hyperglycemia [4]; (iii) formation of Advanced Glycation End Products (AGEs) [5] and (iv) increased oxidative stress [6].…”
Section: Secondary Complications In Diabetesmentioning
confidence: 99%